Examining the Impact of Incorporating Silicon Dioxide Nanoparticles on the Surface Roughness, Surface Hardness, Tensile Strength, and Shear Bond Strength of Chairside Room Temperature Silicone-based Soft Denture Liners: An In-Vitro Study - Wasmaa S. Mahmood; Zainab S Abdullah; Zinah Salah; Abdalbseet A. Fatalla (Wolters Kluwer Medknow Publications, 2024)
Introduction: This study aimed to assess the effect of the addition of 1%, 1.5%, and 2% by weight silicon dioxide nanoparticles on the surface roughness, surface hardness, tensile strength, and shear bond strength of chairside room temperature silicone-based soft denture liners. Methods: SiO2 nanoparticles (NPs) were added to the soft liner in different concentrations: 0% (control group), 1%, 1.5%, and 2% by weight; surface roughness was measured by profilometer, surface hardness, tensile strength, and shear strength were measured by Instron testing machine. Results: Statistically significant differences were found among study groups regarding surface roughness (p = 0.01), surface hardness (p < 0.0001), tensile bond strength (p = 0.002), and shear bond strength (p < 0.0001). Conclusion: The addition of 1.5% SiO2NPs demonstrated an enhancement in shear stress and tensile strength with a decrease in surface hardness and did not affect surface roughness.